An evaluating tool for programming contests - Kósa, Márk; Pánovics, János; Gunda, Lénárd (Teaching Mathematics and Computer Science, 2005)
Students of the University of Debrecen majoring in informatics have been participating in regional ACM international collegiate programming contests since 1995. In earlier times arrangement of the local rounds was difficult because we had to check the contestants' submissions by hand. Beyond the discomfort, this hindered the efficient work of the jury and involved a number of possibilities of making mistakes.The Programming Contest Result Manager (PCRM) program developed in the past two years provides a solution to the above problems. The program automates the evaluation of submissions and provides both the jury and the contestants with a user interface. This application can help the jury not only in ACM type but also in other kinds of practical programming contests.